2018
DOI: 10.1038/s41598-018-31630-z
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in antigenic sites and other functional regions between genotype A and G mumps virus surface proteins

Abstract: The surface proteins of the mumps virus, the fusion protein (F) and haemagglutinin-neuraminidase (HN), are key factors in mumps pathogenesis and are important targets for the immune response during mumps virus infection. We compared the predicted amino acid sequences of the F and HN genes from Dutch mumps virus samples from the pre-vaccine era (1957–1982) with mumps virus genotype G strains (from 2004 onwards). Genotype G is the most frequently detected mumps genotype in recent outbreaks in vaccinated communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 66 publications
3
25
0
1
Order By: Relevance
“…We found that there were numerous fixed differences between samples from the 2016 outbreak and the Jeryl Lynn vaccine strain in regions of immunological significance (S4A Fig and S1 Text), consistent with a recent similar analysis [27]. In the hemagglutinin-neuraminidase (HN) protein, the primary target of neutralizing antibodies [28], we observed 32 sites with fixed amino acid substitutions between our sequences and the Jeryl Lynn strain.…”
Section: Resultssupporting
confidence: 90%
“…We found that there were numerous fixed differences between samples from the 2016 outbreak and the Jeryl Lynn vaccine strain in regions of immunological significance (S4A Fig and S1 Text), consistent with a recent similar analysis [27]. In the hemagglutinin-neuraminidase (HN) protein, the primary target of neutralizing antibodies [28], we observed 32 sites with fixed amino acid substitutions between our sequences and the Jeryl Lynn strain.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, this virus can cause inflammation of the ovaries, testis, pancreas or meninges with several complications. After the introduction of the vaccine against measles, mumps, and rubella (MMR), mumps incidence has decreased, even if several mumps cases have recently been reported [99].…”
mentioning
confidence: 99%
“…There are been reports that the surface PRV proteins, HN and F, are the most antigenic components of other paramyxoviruses (e.g. MuV, Measles virus and PIV5) [ 18 , 20 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…reports that the surface PRV proteins, HN and F, are the most antigenic components of other paramyxoviruses (e.g. MuV, Measles virus and PIV5) [18,20,44]. Currently, several many approaches are being considered to design possible vaccines for PRV.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation